Αγγλικά - Plural Number - Γ'-Δ' Δημοτικού Επ. 72 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική Θα μιλάω αγγλικά. Θα μιλάω σιγά σιγά, ώστε να καταλάβετε όλοι τι θέλω να πω, βασικά. Σήμερα θα μάθουμε τον πληθυντικό των ουσιαστικών, το πλήρων των γνώσεων. Είναι εύκολο, είναι εύκολο, μόνο ακούτε. Μπορείτε να παίξετε γνώσεις με ένα πέντ ή ένα πέντσο ή μπορείτε να προσπαθείτε. Ας ξεκινήσουμε. Γνώσεις. Τι είναι ένα γνώμα? Οι γνώσεις μπορούν να είναι πολλές πράγματα. Μπορούν να είναι άνθρωποι, μια γυναίκα, ένα παιδί, ένα αδερφός, ένα παιδί. Μπορούν να είναι άνθρωποι, ένα γύρο, ένα κατ, ένα μάνα. Μπορούν να είναι φαγητικά, φαγητικά, φαγητικά, όπως μια μπανάνα, ένα άπλο, ένα όραμα. Ή μπορούν να είναι μέρες, όπως μια σχολή, όπως το σπίτι σας. Και υπάρχουν επίπεδες, ένα σχόλιο, ένα σχόλιο, ένα σχόλιο. Λοιπόν, υπάρχουν πολλές, πολλές διαφορετικές γνώματα. Λοιπόν, πώς δημιουργηθούμε το πληθυντικό τους? Πώς χειματίζουμε το πληθυντικό τους. Υπάρχουν 4 βασικά ρούλες και μετά ένα ακόμα στο τέλος που θα δείτε. Ας ξεκινήσουμε από το πρώτο αρχικό με το πρώτο ρούλο. Θα το γράψω εδώ. Ρούλο 1. Απλά προσθέτουμε το σ, στο τέλος του γνώματος. So let's take, for example, a pen, okay, ένα στυλό, a table, an apple, okay. Careful, here we put m, right, because the first letter of this noun is a vowel, a. So the vowels are five in English, a, i, e, o, and u. If we see a vowel, we always put an over here, okay. So what do we do? How do we form the plural? A pen, a table, an apple. Two pens, okay, we just add s. A table, three, tables, again, we just add an s. Or an apple, seven, apples, oops, s, okay. So it's simple, just add s. So a pen, two pens, a table, tables, apple, apples. This is the first rule, okay. Now, let's go to the second one, okay, the second rule. When the noun ends in sh, ch, x, and s, okay, I will add the other one later. What do we do? We put in the end not only s, but es, okay. Let's see some examples. A brush, μια βούρτσα, right, a watch, ένα ρολόι, a box, and a bus. Let's do it over here, να χωρέσουν όλα. So what do we do? A brush, two brushes, brushes, okay. A watch, two watches, again, we put es. A box, two, three, four boxes, and a bus, seven buses, okay. Here we also have nouns that end in o, but αυτά έχουν κάποιες εξαιρέσεις. Ας δούμε όμως τα βασικά, το a tomato, τελειώνει σε o, okay, or a potato, η ντομάτα και η πατάτα basically. We become tomatoes with es again, and potatoes with es. So αυτά έχουν και κάποιες εξαιρέσεις όπως το πιάνω, or το φώτο που παίρνουν απλά es, okay. I'm not going to write them here, απλά να θυμηθείτε αυτά τα βασικά, and there are other rules of course, and many exceptions, but that's okay for now. So let's remember when a noun ends in š, č, x, s, okay, and with o, without the exceptions, we put es, okay, that's rule number two. Now, let's go to the next one. We said before, we only put s and then es, so these are the two first ones. Now, let's learn the other two. So, number three, when the noun ends in consonant and y, okay, consonant remember is σύμφωνο, so if it ends in a consonant plus y, okay, we put i-e-s. For example, let's take a baby, okay, and a party. So, what do we do? A baby, two, they, we take out the y, and we put i-e-s, babies, okay, so we erase the y. Now, a party, for parties, again, we erase the y, and we put i-e-s, parties, but remember, before the end, this has to be a consonant. Πρέπει να είναι σύμφωνο πριν το y, if it's not, αν δεν είναι σύμφωνο, δεν το κάνουμε αυτό. For example, a boy, this is a vowel, right, it's not a consonant, so we don't put i-e-s, we say, let's say three boys, just with an s, like the first rule, okay, because here, this is a vowel, remember the vowels, a-i-e-o and u. So, this is a vowel, so we only put s, this is a consonant, as well as this, so we erase it and we put i-e-s, okay, that's very important to remember. Now, the fourth one, let's write it over here, oops, with the black. So, when the noun has, in the end, f and fe, we put β-e-s in the end, let's see some examples, for example, let's say a leaf, ένα φύλλο, okay, or a wolf, ένας λίκος, or a knife, ένα μαχαίρι, knife. Remember here, we don't pronounce the k, it's knife, not knife, so what happens here, we take out the f again and we put β-e-s, a leaf, two leaves, β-e-s, okay, a wolf, three wolves, β-e-s. And a knife, nein, I'm just writing any number, it doesn't matter, nein, nein, w-z, so we add this in the end. And of course, we erase this, we don't use it, and we put β-e-s, okay, so let's see, a leaf, two leaves again, a wolf, three, four, five, six wolves, and a knife, ten, nine, nein, w-z. So these are the four basic rules, number one, s, number two, e-s, number three, i-e-s, and number four, v-e-s. So these are the four basic ones. Now, we also have some irregular, so what does this mean? Some of them change completely, or they don't change at all. So κάποια αλλάζουν εντελώς ή μπορεί και να μην αλλάξουν καθόλου. Let's see which ones these are. This is the last rule, ο τελευταίος κανόνας, okay? Maybe you can write this down, or you can just look at the board. So number five, what do we have? We have, we put them in categories, maybe, it's easier. Man, ο άντρας, woman, η γυναίκα, child, το παιδί, person, ο άνθρωπος γενικότερα. And let's put here the mouse, είναι και κάποια άλλα, αλλά αυτά είναι τα βασικά, mouse, το ποδήκι. So what happens here? They change completely, αλλάζουν. So man becomes men. One man, two men. We change the a and we put an e. Woman becomes women. Okay? One woman, ten women. Child becomes children. For sure you've heard of this, I'm sure you know it. Then person, people. And mouse becomes mice. Okay? So first category. Second one, tooth, βόδι and foot. Okay? So tooth becomes teeth, double e. You take the double o and you make it into a double e. And the same goes for foot, it becomes feet. So, okay, you see these? We have man, woman, child, person and mouse. And then we have tooth and foot. Okay? So these are very important so that you can remember how we can change them. Okay? And then two stay the same, exactly the same. These are fish, το ψάρι, and sheep, το πρόβατο. Fish becomes fish and sheep becomes sheep. So υπάρχουν και κάποια άλλα, αλλά δεν θα τα μάθουμε τώρα, δεν είναι σημαντικά. Αυτά είναι τα πιο βασικά, the most important ones. So we have man, men, woman, women, child, children, person, people, mouse, mice, tooth, teeth, foot, feet and then the same fish, fish, sheep and sheep. So these are all the rules. One, two, three, four and five. So let's remember them one more time. Rule number one, add S. Rule number two, when we have SH, CH, X, okay, S and O, sometimes we put ES. When we have, number three, when we have consonant plus Y, IES. When we have, number four, F or F and E, we put VES and then the regular ones. Okay? So these are all the rules of the plurals. Now, we can practice together. I will tell you some words and then I will give you some time to think and I will tell you the answer. Okay? So, let me see if you were paying attention. I hope you were. So the first one, let's go with boy. Okay? Then I will write some of them here so you have time to think. Child, let's do box or fish. So I'm mixing everything. Pen and party. Okay? Some examples. Now, let me see how you think the plural is. Boy. What's the plural of boy? Now, there's an O before Y so we don't change it. We just add an S. Boys. Okay? This is a vowel, careful. If there was a consonant, we would erase it and put IES. Number two, child. Child is irregular so we change it. Child becomes children. Okay? One child, ten children. Box. Okay, I'm giving you some time to think. Maybe you can write it down. I would recommend you wrote it down. You can write it on your notebook. Γράψτε τα ίσως στο τραδιό σας για επανάληψη. Box. It ends in X. So, you add ES. Boxes. Alright? Okay. Fish. Everyone says fishes. Actually, sometimes people use it as well but the rule says that it stays the same. Fish. Fish. I hope you guessed it. Now, pen. What happens to pen? I think it's easy. Pen, you just add an S. Pens. Okay? And then the last one over here, party. Party has a consonant over here like we said so we erase the Y and we put IES. Parties. Okay? So, you see some examples. Okay. Now, I hope you wrote them down. I gave you some time. So, last time, let me say them all very, very quickly so that everyone can fully understand it. Να τα καταλάβετε θα τα πω άλλη μια φορά πολύ γρήγορα. Okay? The four first ones. The regular, okay, you have to learn them in the end. So, number one. Just put S. Right? Excellent. Pen, pens, marker, markers, board, boards, table, tables, etc. Number two. When we have, right, S in the end, SH, CH, X, okay, and O sometimes, we put in the end ES. Okay? Box, boxes, fox, foxes, potato, potatoes, brush, brushes. So, dress, dresses, right? There are many words. Number three. Consonant and Y. We erase the Y and we put IES. Only with consonants. Don't forget. So, like baby, babies, party, parties. Careful with consonants. And number four. F and FE in the end. You put BZ. Okay? These are the basic ones. And then the regular ones that we said. That man, men, woman, women, child, children, person, people, mouse, mice. And then we have foot, feet, tooth, teeth. And finally, fish, fish and sheep, sheep. These are the most basic, the most important irregular ones. Okay? So, I hope you understood all of these rules. What you could do is you could practice at home. You can watch this again. You can take notes. Maybe you can write everything on your notebook. I would suggest that. If you write all the rules on your notebook, it will be much easier for you to remember them. And you can practice every day. Now that you have some time, you can practice with all the plurals. So, I hope you understood everything. Ελπίζω να τα καταλάβατε. And I hope that you have a wonderful day. And maybe I will see you again soon. Have a nice day!